Economic Decisions by Approved Principles: Rules of Thumb as Behavioral Guidelines - Walter Buhr; Thomas Christiaans (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2000)
We discuss the relevance of the concept of rational behavior in economic theory and suggest, on the basis of modern brain research results, to abstain from this notion and instead to apply behavioral rules of thumb in decision-making, especially if these rules can be derived from rational problem solutions determined by individual economic agents. We give an example for our point of view which refers to a contribution by Baumol and Quandt on the pricing behavior of a monopolistic firm and which also emphasizes the general importance of dynamic analysis in economics.
Keywords: 330